Language Teacher Agency (Bloomsbury Publishing (UK), 2026)
This open access book argues that language teacher agency is not simply a matter of individual choice, but is also shaped by the complex social, political and educational contexts in which language teachers work. It provides a framework for understanding the complexities of language teacher agency in a wide range of language. It offers practical advice on how to support language teachers in developing and enhancing their agency towards social, cultural, political and linguistic discourses and practices that have an impact on language teachers’ efficacy, intentionality, self-reflectiveness and identity. Through a wide range of methodological approaches such as (duo)ethnographic work, pedagogical interventions, narrative case studies, dialogic approaches and curriculum innovations, this book critically examines the individual and collective efforts of languages teachers as they build and exercise their agentic capacity within and across the contextual conditions in which they are situated. Part I considers the socio-cultural and socio-political factors which facilitate, or interfere with, the exercise of teacher agency in language classrooms, and the ways language teachers can exercise their agency to design locally relevant pedagogies. Part II examines the structural, systemic, ideological and pedagogical transformations needed in order for language teachers to be empowered to displace dominant pedagogies with more socially-just pedagogies to meet the needs of diverse students and of the curriculum. Finally, Part III looks at what dialogic practices can assist language teachers in mitigating dominant discourses and structural procedures, as well as what professional support is needed to assist language teachers in developing a sense of agency. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the University of New England, Australia; University of Melbourne, Australia; and Monash University, Australia.